2011
DOI: 10.5194/bg-8-2461-2011
|View full text |Cite
|
Sign up to set email alerts
|

Labile Fe(II) concentrations in the Atlantic sector of the Southern Ocean along a transect from the subtropical domain to the Weddell Sea Gyre

Abstract: Labile Fe(II) distributions were investigated in the Sub-Tropical South Atlantic and the Southern Ocean during the BONUS-GoodHope cruise from 34 to 57° S (February–March 2008). Concentrations ranged from below the detection limit (0.009 nM) to values as high as 0.125 nM. In the surface mixed layer, labile Fe(II) concentrations were always higher than the detection limit, with values higher than 0.060 nM south of 47° S, representing between 39 % and 63 % of dissolved Fe (DFe). Apparent biological production of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 111 publications
1
27
0
Order By: Relevance
“…Measurements of DFe redox speciation (DFe II and total DFe from which DFe III can be computed) during the BGH cruise provide the opportunity to evaluate the effect of the iron redox state on its isotope signature in the open ocean. These data show that Fe(II) accumulation mostly occurs close to the surface, but not at intermediate depths (26). This mismatch between measured iron redox state and isotopic composition demonstrates that local iron reduction-at the time and location of sampling-was not responsible for the observed intermediate depth δ 56 DFe minimum.…”
Section: Discussionmentioning
confidence: 76%
“…Measurements of DFe redox speciation (DFe II and total DFe from which DFe III can be computed) during the BGH cruise provide the opportunity to evaluate the effect of the iron redox state on its isotope signature in the open ocean. These data show that Fe(II) accumulation mostly occurs close to the surface, but not at intermediate depths (26). This mismatch between measured iron redox state and isotopic composition demonstrates that local iron reduction-at the time and location of sampling-was not responsible for the observed intermediate depth δ 56 DFe minimum.…”
Section: Discussionmentioning
confidence: 76%
“…Sarthou et al (2011) showed that higher values of labile Fe(II) were found in the surface mixed layer than in deep waters toward high latitudes, which could be attributed to atmospheric Fe(II) deposition . Gao et al (2013) reported that total dissolvable Fe airÁsea deposition fluxes were 0.007Á0.52 mg m (2 yr (1 over the SO.…”
Section: Implication For Aerosol Impacts On Climate and Biogeochemicamentioning
confidence: 99%
“…One exception was the humic/fulvic spiked experiment (Table 2), where 32 nM TdFe remained in suspension at the end of the experiment which most likely indicated the presence of more stable Fe(III)-organic complexes or colloids (Kuma et al, 1998) following Fe(II) oxidation. All the experiments used relatively high spikes of Fe(II) (5.2 to 31 nM) which was necessary to keep the Fe(II) concentration above the detection limit ( (Ussher et al, 2007;Sarthou et al, 2011), our experimental conditions ( Table 2) form a reasonable representation of conditions within tropical OMZs where Fe(II) concentrations on the order of 10-100 nM can be found in coastal waters (Hong and Kester, 1986;Lohan and Bruland, 2008;Vedamati et al, 2014).…”
Section: Summary Of Seawater Methods Comparison Experimentsmentioning
confidence: 99%
“…As discussed further in prior work Sarthou et al, 2011), there are multiple reasons why these calculated rate constants are for indicative purposes only (e.g., O 2 may have changed over the duration of the experiments, the effect of DOC is not accounted for in this simple rate equation, the contribution of H 2 O 2 to the oxidation rate was likely nonnegligible, and the values derived from Roy and Wells (2011) are not corrected for small discrepancies in salinity or temperature). Yet, the differences between the luminol and ferrozine based methods are striking nonetheless (Figure 5).…”
Section: Derivation Of Apparent Oxidation Rate Constantsmentioning
confidence: 99%
See 1 more Smart Citation